Board Characteristics and Firm Performance: Evidence from Manufacture Sector of Jordan - Amedi, Ari Muhammad Rashid; Mustafa, Aree Saeed (Accounting Analysis Journal, 2020)
The objective of the study is to investigate the impact of the board of directors’ features on the financial performance of companies, which is measured using return on equity. This study utilized secondary data approach. A population is all companies listed in Amman Stock Exchange (ASE), while the sample consists of all Jordanian companies from manufacture sector from 2016 to 2018. Multiple regression has been used to test this study hypothesis and meet its objective. This study finding aligns with agency theory and resource dependence theory propositions, that the size of the board of directors is negatively related to firm performance. On the other hand, the board of directors' independence and female directors are having a positive influence on firm performance. Finally, this study recommends future studies in Jordan to include all sectors of capital market of Jordan and other corporate governance variable such as ownership structure and examine its influence in the relationship between the board of directors' features and firm performance. Keywords: Board Characteristics; Firm Performance; Jordan